A Juridical Review of Breach of Contract in Commercial Cooperation Agreements in Indonesia - Kadafi, Alsa Ahmad; Hastuti, Rina; Iqbal, Mohammad (Lembaga Publikasi Ilmiah Nusantara, 2025)
Trade cooperation agreements are essential legal instruments in the Indonesian business landscape, as they regulate the rights and obligations of the involved parties. However, in practice, breaches of contract or wanprestasi frequently occur, resulting in losses for one of the parties. This study aims to analyze the legal perspective on wanprestasi in trade cooperation agreements, including its forms, causes, and available legal remedies. The research employs a normative juridical method with a statutory and case study approach. The findings indicate that wanprestasi may take the form of failure to perform, delay, improper performance, or total non-performance. Legally, the aggrieved party may pursue compensation, contract cancellation, performance enforcement, or a combination thereof, as stipulated in Articles 1243 to 1252 of the Indonesian Civil Code. To minimize the risk of wanprestasi, it is recommended that parties formulate clear and detailed agreements with dispute resolution clauses. Effective enforcement of civil law is also essential to ensure legal certainty and protection in commercial activities.